2012
DOI: 10.1080/0964704x.2011.595653
|View full text |Cite
|
Sign up to set email alerts
|

A History of Acute Bacterial Meningitis

Abstract: Although meningitis was not yet known as such, its symptoms have been conceptualized in different ways and many theories about its causes have been formulated in the course of time. Terms like hydrocephalus and brain fever were used for different clinical manifestations of what today would be recognized as meningitis. Pathological-anatomical findings led to the emergence of the clinical entity from several old concepts of disease. Initially, diagnostic means were limited and therapeutic methods did not differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…An important source for these articles was August Hirsch's (1866) [10] monograph on epidemic cerebrospinal meningitis. The period of search was limited to the 19th and early 20th centuries for reasons with respect to the identification of HL (problems with term-condition association), as well as with respect to diagnosing bacterial meningitis, which also gradually came to the foreground in the course of the 19th century [11]. Quotes were translated by the present author.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An important source for these articles was August Hirsch's (1866) [10] monograph on epidemic cerebrospinal meningitis. The period of search was limited to the 19th and early 20th centuries for reasons with respect to the identification of HL (problems with term-condition association), as well as with respect to diagnosing bacterial meningitis, which also gradually came to the foreground in the course of the 19th century [11]. Quotes were translated by the present author.…”
Section: Methodsmentioning
confidence: 99%
“…Recognizing today the diagnosis of bacterial meningitis in texts published prior to 1800 is quite difficult as these texts were still written in terms of the ancient humoral pathophysiology [11]. Even the Strasbourg physician Gabriel Tourdes (1810-1900) [15] experienced difficulties recognizing previous epidemics.…”
Section: Type Of (Bacterial) Meningitismentioning
confidence: 99%
See 1 more Smart Citation
“…PM is one of the most common infections of the Central Nervous System (CNS). It is characterized by fever, headache, stiff neck, nausea, vomiting, photophobia, and altered consciousness [1] . Studies have shown that the annual incidence of meningitis in the United States is 2-10/100000 [2] .…”
Section: Introductionmentioning
confidence: 99%
“…-Casos co-primarios: aquellos casos que tienen lugar en un grupo de contactos próximos con inicio de síntomas de enfermedad en menos de 24 horas; -Caso secundario: aquel caso que tiene lugar en un contacto próximo a un caso primario, tras 24 horas o más del inicio de síntomas en el caso primario. La definición de casos co-primarios limitaba el tiempo hasta 31 días, debido a que se había observado que hasta el 90% de los casos secundarios se producían en las dos semanas siguientes a la aparición del primer caso, pero recientemente se ha constatado que la mitad de los casos secundarios aparecen después de A principios del S. XX comenzaron los primeros intentos de prevenir la enfermedad mediante la administración de sueros intravenosos, que consiguieron reducir la mortalidad de la enfermedad hasta en un 18% en Alemania, o hasta un 33% desde un punto de vista global, según Flexner 16 . La sueroterapia fue posteriormente sustituida por el empleo de antibióticos, que comenzó con la introducción de las sulfonamidas.…”
Section: Introductionunclassified